Metagenomics Shows That Low-Energy Anaerobic−Aerobic Treatment Reactors Reduce Antibiotic Resistance Gene Levels from Domestic Wastewater (2015)
ABSTRACT: Effective domestic wastewater treatment is among our primary defenses against the dissemination of infectious waterborne disease. However, reducing the amount of energy used in treatment processes has become essential for the future. One low-energy treatment option is anaerobic–aerobic sequence (AAS) bioreactors, which use an anaerobic pretreatment step (e.g., anaerobic hybrid reactors) to reduce carbon levels, followed by some form of aerobic treatment. Although AAS is common in warm climates, it is not known how its compares to other treatment options relative to disease transmission, including its influence on antibiotic resistance (AR) in treated effluents. Here, we used metagenomic approaches to contrast the fate of antibiotic-resistant genes (ARG) in anaerobic, aerobic, and AAS bioreactors treating domestic wastewater. Five reactor configurations were monitored for 6 months, and treatment performance, energy use, and ARG abundance and diversity were compared in influents and effluents. AAS and aerobic reactors were superior to anaerobic units in reducing ARG-like sequence abundances, with effluent ARG levels of 29, 34, and 74 ppm (198 ppm influent), respectively. AAS and aerobic systems especially reduced aminoglycoside, tetracycline, and β-lactam ARG levels relative to anaerobic units, although 63 persistent ARG subtypes were detected in effluents from all systems (of 234 assessed). Sulfonamide and chloramphenicol ARG levels were largely unaffected by treatment, whereas a broad shift from target-specific ARGs to ARGs associated with multi-drug resistance was seen across influents and effluents. AAS reactors show promise for future applications because they can reduce more ARGs for less energy (32% less energy here), but all three treatment options have limitations and need further study.